Reversible Supramolecular Surface Attachment of Enzyme–Polymer Conjugates for the Design of Biocatalytic Filtration Membranes. (13th October 2015) - Moridi, Negar; Corvini, Philippe F.‐X.; Shahgaldian, Patrick
Abstract: To be used successfully in continuous reactor systems, enzymes must either be retained using filtration membranes or immobilized on a solid component of the reactor. Whereas the first approach requires large amounts of energy, the second approach is limited by the low temporal stability of enzymes under operational conditions. To circumvent these major stumbling blocks, we have developed a strategy that enables the reversible supramolecular immobilization of bioactive enzyme–polymer conjugates at the surface of filtration membranes. The polymer is produced through a reversible addition–fragmentation transfer method; it contains multiple adamantyl moieties that are used to bind the resulting conjugate at the surface of the membrane which has surface‐immobilized cyclodextrin macrocycles. This supramolecular modification is stable under operational conditions and allows for efficient biocatalysis, and can be reversed by competitive host–guest interactions. Abstract : Enzyme in der Membran : Die reversible Biokonjugation an der Oberfläche einer Filtermembran gelingt über ein neues Enzym‐Polymer‐Konjugat mit mehreren Adamantyleinheiten. Diese supramolekulare Modifikation ist als Teil eines Membranbioreaktors stabil unter Betriebsbedingungen und ermöglicht eine effiziente Biokatalyse.